2019 International Conference on Robotics and Automation (ICRA) 2019
DOI: 10.1109/icra.2019.8794222
|View full text |Cite
|
Sign up to set email alerts
|

UWB/LiDAR Fusion For Cooperative Range-Only SLAM

Abstract: We equip an ultra-wideband (UWB) node and a 2D LiDAR sensor a.k.a. 2D laser rangefinder on a mobile robot, and place UWB beacon nodes at unknown locations in an unknown environment. All UWB nodes can do ranging with each other thus forming a cooperative sensor networks. We propose to fuse the peer-to-peer ranges measured between UWB nodes and laser scanning information, i.e. range measured between robot and nearby objects/obstacles, for simultaneous localization of the robot, all UWB beacons and LiDAR mapping.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(45 citation statements)
references
References 24 publications
0
45
0
Order By: Relevance
“…This algorithm falsely estimated that the robot had arrived at entrance of the hall (indicated by the green arrow in Figure 6B); however, the ground truth position of the hall's entrance was at the intersections between the paths and the white vertical line in Figure 6B. Similar cases of poor estimation in long corridors have been discussed in the study of Song et al (2019).…”
Section: Resultsmentioning
confidence: 54%
“…This algorithm falsely estimated that the robot had arrived at entrance of the hall (indicated by the green arrow in Figure 6B); however, the ground truth position of the hall's entrance was at the intersections between the paths and the white vertical line in Figure 6B. Similar cases of poor estimation in long corridors have been discussed in the study of Song et al (2019).…”
Section: Resultsmentioning
confidence: 54%
“…Note that the power consumption presented is for the overall system including the sensors. As can be seen from Table II, only UWB-LiDAR [17] matches the accuracy and latency provided by FEEL, however this comes at the expense of high power consumption and overall system cost since it employs LiDAR. The missing details of [9] is due to the insufficient details provided in the article.…”
Section: B Experimental Resultsmentioning
confidence: 93%
“…For instance, the integration of the radio frequency identification (RFID) technology with GPS-based technologies are reviewed to enhance outdoor tracking of resources [12,13]. Data fusion of imaging technologies (e.g., laser scanning and photogrammetry) with technologies such as RFID, UWB, and GPS have also been investigated recently [14,15].…”
Section: Overview Of Research On Automated Site Data Acquisitionmentioning
confidence: 99%
“…In fact, by having a better visualization model of a site and real-time information for progress reporting and schedule updating, it is possible to provide more robust and timely information for an earned value analysis (EVM) [6,15,28]. For instance, researchers in [15] integrated a 2D laser scanner with a UWB system in order to improve their simultaneous localization and mapping (SLAM) algorithm for localization of a moving robot. They demonstrated that this integration provides better visualization of the site due to its ability to accurately measure the range to nearby objects.…”
Section: Point Cloud Data Fusion With Uwb Datamentioning
confidence: 99%